Dampak Pengelolaan Limbah RSI Jemursari Surabaya Terhadap Eksternalitas Ditinjau Dari ESDAL Islam - Arisma Sari; Moh. Qudsi Fauzy (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This study aims to identify and explain the impact of waste management in Jemursari Islamic Hospital of Surabaya to externalities in terms of economic resources and the environment in the Islamic perspective. This study used a qualitative approach with case study strategy. The data collection was conducted using interviews and direct observation to the object of research.The results showed a positive impact on the management of waste Islamic Hospital Jemursari Surabaya to eskternalitas shown not to appear strong odors from waste management and the environment in hospital becomes cleaner. The results of the analysis of benefits and costs calculation in 2010 to 2015 shows the NPV> 0 and BCR> 1%, means that the value of the benefit is greater than the costs incurred, and waste management projects feasible.